Single-sided NMR - Casanova, Federico; Perlo, Juan; Blümich, Bernhard (Springer, 2011)
The use of conventional nuclear magnetic resonance is limited by the fact that the object needs to be carried to the NMR equipment and needs to fit inside large superconducting magnets. Both limitations are removed by single-sided NMR probes based on open magnets specially adapted to the object under study. These can be inexpensive and portable sensors that give access to a large number of applications inaccessible with using conventional magnet geometries. Substantial improvements in the magnet design, detection electronics, and the implementation of suitable techniques to work in the inhomogeneous magnetic fields of open magnets have allowed scientists and engineers to measure relaxation-time distributions, diffusion coefficients, 3D images, velocity distributions, and even highly resolved NMR spectra in the stray field of the magnet. This book is the first comprehensive account describing the key issues to be considered at the time of designing and building open magnets, and summarizing the arsenal of pulse sequences available today for material analysis.